Synthesis of Sialic Acids, Their Derivatives, and Analogs by Using a Whole‐Cell Catalyst. Issue 60 (9th October 2017) - Lv, Xun; Cao, Hongzhi; Lin, Baixue; Wang, Wei; Zhang, Wande; Duan, Qian; Tao, Yong; Liu, Xue‐Wei; Li, Xuebing
Abstract: Sialic acids (Sias) are important constituents of cell surface glycans. Ready access to Sias in large quantities would facilitate the development of carbohydrate‐based vaccines and small‐molecule drugs. We now present a facile method for synthesizing various natural forms and non‐natural derivatives or analogs of Sias by using a whole‐cell catalyst, which is constructed by adding a plasmid containing necessary enzyme genes into a metabolically engineered strain of Escherichia coli . The flexible substrate tolerance of incorporated enzymes ( N ‐acetylglucosamine 2‐epimerase and N ‐acetylneuraminic acid aldolase) allows the cellular catalyst to convert a wide range of simple and inexpensive sugars into various Sia‐related compounds through an easily scalable fermentation process. Further, syntheses using this whole‐cell biotransformation in combination with three conventional enzymatic reactions provide a series of complex Sia‐containing glycans (sialyloligosaccharides) and their derivatives bearing different substituents. The processes described herein should permit the large‐scale and economical production of both Sias and sialyloligosaccharides, and may complement existing chemical and enzymatic strategies. Abstract : Sialic acid‐producing cell factory : Engineered Escherichia coli converted simple and inexpensive sugars into various natural forms and non‐natural derivatives or analogs of sialic acid through an easily scalable fermentation process. Syntheses using this cellular catalyst in combination with conventional enzymes afforded a range of complex sialyloligosaccharides without isolation of intermediates.